Changes in air quality in‐taxis and in working conditions of taxi drivers pre‐ and post‐lockdown, during the COVID‐19 pandemic in the Paris area. (5th December 2021) - Hachem, Melissa; Bensefa‐Colas, Lynda; Momas, Isabelle
Abstract: We evaluated the impact of the lockdown restriction measures in the Paris area on the variation of in‐vehicle ultrafine particle (UFP) and black carbon (BC) concentrations between the pre‐ and post‐lockdown period and professional drivers' working conditions and practices. The study was conducted with 33 taxi drivers. UFP and BC were measured inside their vehicles with DiSCmini ® and microAeth ®, respectively, on two typical working days pre‐ and post‐lockdown. Job characteristics were self‐reported. Our results showed that post‐lockdown, both the number of clients and journey duration significantly decreased. Taxi drivers opened their windows significantly more and reduced the use of air recirculation. UFP decreased significantly by 32% and BC by 31% post‐lockdown, with a weaker positive correlation compared to pre‐lockdown. The reduction of in‐vehicle UFP was due mainly to the reduction of traffic flow and ventilation settings, though the latter probably varied according to traffic conditions. The variation of in‐vehicle BC also tended to be related to the decrease in traffic flow post‐lockdown. We emphasize the role of traffic emissions on in‐vehicle air pollution and that preventive measures such ventilation settings would help to minimize the exposure of professional drivers and passengers to air pollutants.